Too much money : a novel - Dunne, Dominick. frey50 (New York : Crown Publishers, 2009)
High-society journalist Gus Bailey is caught in the middle of two stressful situations. The first is an $11 million slander suit from a powerful congressman he accused of being involved in the mysterious disappearance of a young women. The second is the book on the suspicious death of a billionaire with too many unanswered questions that he's been contracted to write. He's afraid failure in either situation will mean the end of him.
Keywords: Authors; Older men; Rich people; Socialites; New York (N.Y.) -- Social life and customs